Neutron investigations of the processes of self-diffusion of molecules in the heavy water-glycerol system as functions of the temperature and concentration - Vasylkevych, O.A.; Slisenko, V.I. (Reports of the National Academy of Sciences of Ukraine, 2018)
The results of studies of the self-diffusion of glycerol molecules in a solution of heavy water-glycer ol at two concentrations x = 0.046 molar fractions and x = 0.055 mol. f. in the temperature range 2-10 °C by the method of quasi-elastic scattering of slow neutrons are presented. The values of the total coefficient of self-diffusion and its one-particle and collective components are obtained. Anomalous behavior has been revealed in their temperature dependence: at T = 3 °C and the solution concentration, especially at x = 0.046 mol. f., a deep minimum is observed. Herewith. the lifetime of glycerol molecules in the vibrational state increases substantially. This can be explained by the fact that glycerol molecules at a given temperature and concentration effectively bind water molecules, forming complexes and thereby reducing their mobility. The change in the concentration of glycerol molecules to 0.055 mol. f. leads to a sharp increase (by 40 %) in the intensity of diffusion processes.